PENDIDIKAN AGAMA ISLAM BERBASIS SIRAH NABAWIYAH - Toha Makhshun (Universitas Islam Sultan Agung, 2020)
The article aims to explain and describe the concept of Islamic education which imitates the Prophet's model in educating friends. The method used is descriptive qualitative analysis, namely describing the data accompanied by critical analysis. The results of the research can be concluded that in general, Islamic religious education based on sirah Nabawiyah at the Kuttab Al-Fatih Semarang Foundation is carried out by teachers very well and efficiently, this can be proven from several things, namely: 1). Planning Based on Sirah Nabawiyah at the Kuttab Al-Fatih Semarang Foundation can be said to be very good and efficient, because in implementing planning in learning Kuttab teachers really pay attention to the procedures that will be used and applied to good students. 2) The implementation of Islamic Learning Based on Sirah Nabawiyah at the Kuttab Al-Fatih Semarang Foundation is very good and efficient, because most of the indicators contained in learning have been carried out by the teacher both from the aspects of preliminary activities, core activities, and closing activities are in accordance with Kuttab procedures.Keywords: Islamic Education, Sirah Nabawiyah